The evaluation of efficiency and value addition of IFRS endorsement towards earnings timeliness disclosure. (3rd August 2020) - Mohsin, Muhammad; Nurunnabi, Mohammad; Zhang, Jijian; Sun, Huaping; Iqbal, Nadeem; Iram, Robina; Abbas, Qaiser
Abstract: Measurement of accounting information under International Financial Reporting Standards (IFRS) plays an important role in the determination of earnings timeliness information and investor's decision making. This study assessed the compulsory acceptance of IFRS adoption. The study also measures the efficiency of Pakistani banking sector. We employed data envelopment analysis, SVAR and regression methods to measure Pakistani banks efficiency. The results show that the mandatory adoption of IFRS has increased earnings timeliness of information in all banks. The assessment of cumulative effect on banks by incorporating single weighted index value (ET index) reveals that IFRS increased timely profit and loss realization of banks. Comparatively the bank‐wise estimation of earning timeliness indices shows that IFRS does not shows a significant impact on earnings timeliness of commercial and specialized banks. Finally, the evaluation of IFRS policy shocks shows that earnings timeliness and stock returns are positively responding to change in reporting policy. Furthermore, we anticipate policy change to overcome the gap between asymmetrical earnings exposure and value relevancy of investors decision.